A numerical study of measurement uncertainties for wave gauges. (December 2021) - Coelho, Gustavo Esteves; Ribeiro, Álvaro; Neves, Maria Graça; Pascoal, António
Abstract: This study describes the development of a Monte Carlo based numerical analysis method to determine the instrumental uncertainty of dimensional measurements with wave gauges. The paper presents the adopted calculation procedure, namely, the mathematical model used in the determination of the amplitude and frequency of the wave gauge measurements. The results show a relative expanded (95%) target instrumental measurement uncertainty between 0.067 7 m and 0.068 2 m for the amplitude and between 0.592 4 Hz, and 0.592 8 Hz for the frequency. The study carried out allows for the conclusion that the use of a Monte Carlo-based numerical approach is suitable to evaluate the measurement uncertainty of parameters fitted to wave displacement analysis.